Improving Signature Behavior by Irrevocability in Transactional Memory Systems - Quislant, Ricardo; Gutierrez, Eladio; Zapata, Emilio L.; Plata, Oscar (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2014)
Signatures have been proposed in Hardware Transactional Memory (HTM) to represent read and write sets of transactions and decouple transaction conflict detection from private caches. Generally, signatures are implemented as Bloom filters that allow unbounded read/write sets to be summarized in bounded hardware, at the cost of address aliasing that causes false conflict detection. Such conflicts rises exponentially as signature fills so they can lead a parallel program to perform worse than its sequential counterpart (we say that signature saturates). In this work, irrevocability is proposed to address the signature saturation problem. When a transaction is near to saturate its signature, the transaction enters an irrevocable state that prevents it from being aborted. Then, such a transaction keeps running while the others are either stalled or allowed to run concurrently. Two variants of irrevocability are analyzed in this paper. Experimental evaluation on an HTM simulator shows the benefits in performance and power consumption of the proposed irrevocability mechanisms.